1925-1929 m. tarptautinės ir Lietuvos politikos klausimai - Kasperavičius, Algis (Lietuvos istorijos studijos, 1996)
Petras Klimas (1891-1969) was one of the creators of independent Lithuania, as well as a historian and diplomat. In 1925-1940, he was the ambassador of the Republic of Lithuania in Paris. The reports of diplomats in their native states are a very important historical source. The largest number of P. Klimas’s reports are kept in the Lithuanian State Archives. They are full of information and estimation, which help one better understand the international and internal situation in Lithuania at that time. In confidential reports, P. Klimas used the opportunity to express his independent opinion, which sometimes contradicted the politics and propaganda of the official Lithuanian authority. In the reports, most attention was paid to the attitude of the power of France, people, and mass media on the argument between Lithuania and Poland with respect to Vilnius. The struggle between two arguing states was reflected in them. In this struggle, both Lithuanian and Polish diplomats tried to turn French public opinion to their own advantage, sometimes granting subsidies to some newspapers and journalists. The Poles had larger financial possibilities and influence on French public opinion. Poland was the most important ally of France in Eastern Europe. P. Klimas cited the words of one influential journalist: "Poland never gives Vilnius to Lithuania. Thus, the actions of the French in this direction would mean the instigation of their ally without any necessity." In these conditions, it was difficult for the Lithuanian diplomats to disregard hostile propaganda and disinformation spread by the Poles. The French public opinion malevolently reacted to the coup in Lithuania on December 17, 1926, the liquidation of parliamentarianism, and the strict measures in respect to opposition. That’s why the French mass media benevolently reacted to the resignation of A. Voldemaras, whom the French considered the culprit of the politics of repressions, from the post of Prime Minister in August, 1929. Personally, P. Klimas didn’t support the strict measures, but he tried to serve Lithuania, not one or another political trend. He didn’t see an alternative to the nation’s power.